Off-season cabbage-based cropping systems are remunerative in Himachal Pradesh - Rahi, Shakuntla; Choudhary, Anil K (Indian Horticulture, 2015)
Off-season cabbage production has become a boon to hill farmers in Himachal Pradesh in general and in high hill wet temperate region of Mandi district in particular. Standardized technology of KVK, Mandi to shift general cultivation time of offseason cabbage from April–June to June–November has opened a choice of new cropping systems, viz. cabbage (April–June) – peas (July–November), cabbage (June–November) – peas (December–April/May), cabbage (June–November) – potato (March– June) to hill farmers. The KVK, Mandi has transferred this technology of profitable production systems in intensive manner during 2006-2012 among hill farmers through appropriate technology transfer. Today, farmers of wet temperate high hill region of Seraj, Gohar and Karsog blocks of Mandi district are practising these cropping sequences. With sound technical back-up of KVK, Mandi, these cropping systems have become most remunerative for hill farmers on their small and staggered land holdings. This success story has brought winds of change in hill farming and rural livelihood in this remote region of Mandi district.